Modelling and Optimisation of Resilience and Corrosion Rate of Aluminium 7075 Thin Plate during Surface Grinding (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2026)
The main goal of this work is to model and optimise the resilience and corrosion rate of Aluminium 7075 (AA7075) thin plate during surface grinding. AA7075 thin plates were ground with respect to the factorial design schedule, and their resilience and corrosion rate were determined from the DI-CP/V2 servo-hydraulic testing machine and the CS series electrochemical workstation, respectively. The Minitab statistical tool was utilised to analyse the data. Statistical analysis revealed that feed rate (absolute standardised effect = 8.68) and table speed (6.81) are the most influential factors affecting resilience, while the feed–grinding depth interaction (2.78) also contributes significantly. The interactions between table speed and feed, and between table speed and grinding depth, were not significant. For corrosion rate, feed and its interaction with grinding depth exhibited the strongest influence (10.94), followed by table speed (6.37) and the three-factor interaction (2.34), whereas other interactions were insignificant. The resilience model demonstrated good predictive capability (R² = 83.64%, adj. R² = 75.22%, pred. R² = 61.05%), while the corrosion rate model showed excellent predictive accuracy (R² = 99.20%, adj. R² = 98.42%, pred. R² = 96.78%). The optimal conditions were found to be low table speed (2.0 spm), low feed (1.0 mm), and moderate grinding depth (0.5 mm) with a composite desirability of 0.817.